Konsep Manajemen Layanan Penempatan dan Penyaluran dalam Bimbingan dan Konseling - Bakhrudin All Habsy; Aulia Rizkika Saraswati; Mutiara Azizah; Khairunisha Nabila Yahya; Nuris Sa’idah Rahmah Maulidiyah; Muhammad Yunus Effendi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Placement and channeling service management in guidance and counseling is a systematic approach that aims to help individuals find the right path in education, career, and social life. This concept involves several key components, including identification of counselee needs, evaluation of potential, and development of an appropriate placement plan. The method used in this research is qualitative with a type of literature study with activities that include searching, reviewing, reading books or journals relevant to the research. The main purpose of this service management is to facilitate the transition process of individuals from education to the world of work, as well as support their personal development. This involves collaboration between counselors, educational institutions, and industry to ensure that clients receive the necessary information and resources. The findings of this study are to discuss (1) Definition of placement and channeling services, (2) Forms of placement and channeling services, (3) Mechanisms of placement and channeling services, (4) Purpose of placement and channeling services, and (5) Assessment of counseling guidance in placement and channeling services. The purpose of this research is to describe and explain the management of placement and channeling services.